Confucianism Its Roots and Global Significance - Lee, Ming-huei (Confucian Cultures, 2017)
In Confucianism: Its Roots and Global Significance, English language readers get a rare opportunity to read the work in a single volume of one of Taiwan's most distinguished scholars. Although Lee Ming-huei has published in English before, the corpus of his non-Chinese writings is in German. Readers of this volume will discover the hard-mindedness and precision of thinking associated with German philosophy as they enter into Lee's discussions of Confucianism. Progressing through the book, they will be constantly reminded that all philosophy should be truly comparative. The work is divided into three parts: Classical Confucianism and Its Modern Re-Interpretations, Neo-Confucianism in China and Korea, and Ethics and Politics. The interrelated ideas and arguments presented here contribute significantly to the Confucian project in English-speaking countries across the world.